Educational Ideas on the Move: Student Teachers’ International Teaching Internship - Juul-Wiese, Thilde (Nordic Journal of Comparative and International Education (NJCIE), 2023)
Based on ethnographic fieldwork amongst Danish student teachers, this paper examines international teaching internships from a mobilities and spatial perspective. While the international teaching internship is regarded as a tool to develop student teachers’ intercultural competencies, this paper shows how culturally shaped educational ideas travel with and are practiced by student teachers in new educational and cultural contexts. Therefore, this paper suggests that such internships may perpetuate and reinforce normative ideas about pedagogy and ‘correct’ ways of teaching, being a pupil, and a teacher. The paper finds that student teachers see some educational ideas and practices as universal and applicable everywhere and others as particular and spatially bound. This, the paper argues, reflects a hierarchisation of ideas based on an assumption of the superiority of ‘Western’ education, which results in processes of pedagogical othering. The paper further argues that international teaching internships represent an important avenue to critically discuss educational values and examine how values impact pedagogical practice, furthering students’ professional development.